2008
DOI: 10.17221/1123-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of seed oils and nutritional compositions of seeds from different varieties of Momordica charantiaLinn.cultivated in Bangladesh

Abstract: Farmers in rural areas of almost all the districts of Bangladesh cultivate different varieties of edible plant karela to satisfy nutritional requirements. Herein, we report on the characteristics of seed oils and nutrients and mineral contents of seeds from three varieties of karela. Most of the physicochemical characteristics were significantly (P < 0.05) affected with the samples tested. Seed oils of all varieties displayed a higher degree of unsaturation and in GLC reported herein, only five fatty acids wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 16 publications
9
27
3
Order By: Relevance
“…While our findings for fruit weight were similar with Mulani et al (2007) results, they were lower than Raja and Shanthi (2009) and Meenakshi et al (2007) findings. Oil and ash contents of the fruit seeds were found to be 33.93-36.21%, 2.25-2.73%, respectively by Ali et al (2008). Ash content showed similarity with this literature values.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…While our findings for fruit weight were similar with Mulani et al (2007) results, they were lower than Raja and Shanthi (2009) and Meenakshi et al (2007) findings. Oil and ash contents of the fruit seeds were found to be 33.93-36.21%, 2.25-2.73%, respectively by Ali et al (2008). Ash content showed similarity with this literature values.…”
Section: Resultssupporting
confidence: 81%
“…Ash content showed similarity with this literature values. On the other hand, oil content was lower than Ali et al (2008) findings. Horax et al (2010) found the oil content of the seed was 18.1% for mature fruit and 36.51% for ripe fruit.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Smoke point of S. mahagoni seed oil could not be determined due to the oil low burning characteristics, soaking tendency, fluidity, etc. Flash and fire points as determined from T. anguina seed oil (331 and 361 °C) were higher than those of the experimental sample S. mahagoni (90 and 100 o C) and of tobacco seed oil (142 and 162 °C) [31]. Cloud and pour points of S. mahagoni seed oil (6 and −6 °C) appeared to be higher than the values estimated from the experimental sample T. anguina (1.10 and −7 °C) and also from the tobacco seed oil (−15 and −18 °C) detected by Abbas Ali et al [31].…”
Section: Physico-chemical Characteristicsmentioning
confidence: 56%